Accuracy of Pretransplant Imaging Diagnostic for Hepatocellular Carcinoma: A Retrospective German Multicenter Study - Uta Herden; Wenzel Schoening; Johann Pratschke; Steffen Manekeller; Andreas Paul; Richard Linke; Thomas Lorf; Frank Lehner; Felix Braun; Dirk L. Stippel; Robert Sucher; Hartmut Schmidt; et al. (Canadian Journal of Gastroenterology and Hepatology)
Selection and prioritization of patients with HCC for LT are based on pretransplant imaging diagnostic, taking the risk of incorrect diagnosis. According to the German waitlist guidelines, imaging has to be reported to the allocation organization (Eurotransplant) and pathology reports have to be submitted thereafter. In order to assess current procedures we performed a retrospective multicenter analysis in all German transplant centers with focus on accuracy of imaging diagnostic and tumor classification. 1168 primary LT for HCC were conducted between 2007 and 2013 in Germany. Patients inside the Milan, UCSF, and up-to-seven criteria were misclassified with definitive histologic results in 18%, 15%, and 11%, respectively. Patients pretransplant outside the Milan, UCSF, and up-to-seven criteria were otherwise misclassified in 34%, 43%, and 41%. Recurrence-free survival correlated with classification by posttransplant histological report, but not pretransplant imaging diagnostic. Univariate analysis revealed tumor size, vascular invasion, and grading as significant parameters for outcome, while tumor grading was the only parameter persisting by multivariate testing. Conclusion. There was a relevant percentage (15-40%) of patients misclassified by imaging diagnosis at a time prior to LI-RADS and guidelines to improve imaging of HCC. Outcome analysis showed a good correlation to histological, in contrast poor correlation to imaging diagnosis, suggesting an adjustment of the LT selection and prioritization criteria.